TECHNOLOGY OF FORMATION OF METHODOLOGICAL CULTURE IN FUTURE TEACHERS BASED ON MODULAR EDUCATION - Rasulova Mastura (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, the author explained the means of modeling objective situations that require the manifestation of methodological culture in students during the educational process, the understanding of its importance in pedagogical activity, and the feeling of its insufficient formation by students themselves.